Development of project-based interactive e-modules in accordance with the IQF integrated curriculum concept in learning organic chemical reactions to improve student chemistry learning outcomes - Bajoka Nainggolan; Anna Juniar; Ramlan Silaban (Jurnal Pendidikan Kimia (JPKIM), 2023)
Project-based interactive learning is the right choice to encourage students to learn actively and effectively to improve their learning outcomes. The aim of the research is to find project-based interactive e-Module teaching materials that are valid, effective, standard, suitable for use. Research stages: Needs analysis; e-Module development; standardization validation; individual, small and large group trials; effectiveness test, and test students' perception of satisfaction. The research uses the ADDIE method. Sample: Curriculum, teaching materials from publishers A and B, expert validators and 45 students. Test the feasibility and effectiveness of the e-Module, measuring the increase in learning outcomes and student satisfaction using test instruments. Data were processed and analyzed descriptively using SPSS. Research findings: the interactive e-Module teaching materials developed are valid, effective and standard, suitable for use. The product was effective in small group trials with student learning outcomes of (M 79.35%), large group (M= 79.85%), high and effective category. Respondents' assessment of the product was very valid, suitable for use (M = 3.81). The student satisfaction index is very satisfied (M = 88.80%). Hypothesis testing with paired ttest obtained sig. 0.011. Because sig < α (0.011 < 0.05), there are differences in post-test and pre-test learning outcomes. In conclusion, the project-based interactive e-Module teaching materials developed are valid, effective, standard, and suitable for use to improve student chemistry learning outcomes.Keywords: Development of interactive; IQF-based curriculum; Project-based; Valid and effective e-modules